Microstructure of zirconium carbide ceramics synthesized by spark plasma sintering - B.A.B. Alawad; H.A.A. Abdelbagi; T.P. Ntsoane; T.T. Hlatshwayo (Materials and Devices, 2022)
Zirconium carbide (ZrC) samples were prepared by spark plasma sintering (SPS), at temperatures of 1700 °C, 1900 °C and 2100 °C, all at pressure of 50 megapascal (MPa). The density of ZrC ceramic pellets was measured using a Micromeritics AccuPyc II 1340 Helium Pycnometer. The density of ZrC ceramic pellets was found to increase from (6.51 ± 0.032) g/cm3 to (6.66 ± 0.039) g/cm3 and (6.70 ± 0.017) g/cm3 when the temperature of the SPS was increased from 1700 oC to 1900 oC and 2100 oC respectively. Moreover, the hardness of ZrC ceramic pellets were measured using Rockwell hardness test. The hardness of ZrC ceramic pellets increased from (7.4 ± 0.83) to (17.0 ± 0.073) and (18.4± 0.05) gigapascals (GPa) at temperatures of 1700 oC, 1900 oC and 2100 oC respectively. X-ray diffraction shows the absence of spurious phases or impurity. XRD results showed that, all prepared ZrC samples has the same preferred orientation of the planes (i.e., 200). Furthermore, the average grain size of ZrC was calculated using Sherrers’s equation. The average grain size of the pure ZrC powder increased from 67.46 nm to 72 nm, 79 nm and 83 nm when the ZrC powder was sinteried at temperatures of 1700 oC, 1900 oC and 2100 oC respectively. The differences in the average grain size between the prepared samples leads to show different surface morphologies that monitored by scanning electron microscopy (SEM).